Variation sur l’autoreprésentation photographique féminine au tournant du siècle - Marie Cordié Levy (Anglophonia)
Turning away from domestic chores, many women became photographers at the end of the 19th century, setting up portrait studios in American cities, while men turned to landscape photography. In order to understand what drove them on, we propose to study a series of self-portraits by three American photographers: Frances Benjamin Johnston, Ann Brigman and Imogen Cunningham, using the method developed by the historian Carlo Ginsburg and the historian of art Aloïs Riegl, which is akin to Bronislav Malinowski’s participative objectivation1.1. Il s’agit de procéder à une lecture de la photographie en partant de l’image elle-même, de rechercher les enjeux même inconscients qui s’y développent, en établissant des correspondances étroites avec la production, la recherche esthétique et les cercles ou réseaux professionnels dans lesquels le/la photographe s’insérait ou développait sa pratique.